Dampak Latar Belakang Sosial Ekonomi Terhadap Akses Pendidikan di SDN 006 Sangatta Utara - Akmaliah, Qatrunnada Jinan; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Socioeconomic background can affect students' ability to access education, both in terms of transportation and the provision of learning supplies. This study aims to identify the impact of family socioeconomic background on access to education at SDN 006 Sangatta Utara. This study uses a qualitative method with a case study approach, which involves interviews with homeroom teachers and direct observation at school. Data collected through interviews with teachers. The results of the study show that the socio-economic condition of the family does not provide a significant obstacle to students' access to education at SDN 006 Sangatta Utara. Most students have adequate transportation facilities, so no student has to walk to get to school. In addition, the majority of students' parents have better-than-average economic conditions, which allows them to meet their children's school supplies needs without any constraints. This is more due to children's behavioral factors than the family's economic limitations